UNDERSTANDING CONSUMER BEHAVIOR WITH COMPULSIVE BUYING DISORDER OF DIAMOND PRODUCTS IN INDONESIA DURING THE COVID-19 PANDEMIC - johnny hadi raharjo (Jurnal MEBIS (Manajemen dan Bisnis), 2022)
Human character is unique, especially in making purchasing decisions about what his "needs" look like. Interestingly, during this pandemic, based on data in the world, the purchase of luxury products tends to decline, and consumers prefer to meet life support products, in order to survive, but this does not apply to some consumers in Indonesia, where in reality there is an increase in purchases of luxury goods, one of which is only diamond products. This behavior is identified as compulsive buying behavior, and to understand the decision-making process both cognitive and affective dissonance of compulsive buyers. This study used an in-depth interview approach and a saturation point method in extracting information, where this research showed that many buyers were motivated by affective factors, and experienced new problems after making a purchase, despite still making repeated product purchases. This study used profiles of subjects from various classes, from the upper class to the lower class, who had obsessive compulsive behaviors on the buying behavior of gem products.